(untitled) (Bangladesh Journal of Otorhinolaryngology, 2011)
Objectives: To find out different etio-pathological factors of the disease and also to rise awareness among all levels of medical practitioners and thus decrease missing of diagnosis by early referral, appropriate surgical intervention, and thereby reduce morbidity and mortality of the patient. Methods: A total of 100 patients with chronic suppurative otitis media (CSOM) were collected from the department of Otolaryngology - Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka Medical College Hospital (DMCH) and Sir Salimullah Medical College and Mitford Hospital Dhaka from January 2003 to February 2004. Patients having CSOM with definitive cholesteatoma with or without complications were included in this study in different age & sex belong to different socioeconomic conditions. Results: One hundred patients of CSOM with cholesteatoma had been included in this study to see the various aspects of the disease with particular attention to know the etiopathology of CSOM with cholesteatoma with or without complications in our perspective. One hundred patients of different age and sex belonging to different socioeconomic conditions were examined meticulously under magnification and investigated as per protocol. The study shows poverty, illiteracy, overcrowding, living in slum with kuntcha floor, bathing in ponds and river with the habit of swimming are the main etiological factors. The study also shows ignorance about primary health care and grave consequences of the disease, nonavailability of trained doctors in the vicinity are also responsible for the development of disease and its complications. Conclusion: The study concluded that by avoiding etiological factors, improving socioeconomic condition & literacy status and by providing trained doctors in the rural areas, the development of the disease & its complications can be reduced and thus saves thousands of lives with early referral and early surgical intervention. Key words: Chronic Suppurative Otitis Media; Cholesteatoma. DOI: 10.3329/bjo.v17i1.7627 Bangladesh J Otorhinolaryngol 2011; 17(1): 42-47